Topographic Mapping of Collagenous Gastritis - Hugh J Freeman (Canadian Journal of Gastroenterology)
A 74-year-old woman was investigated for abdominal pain and diarrhea. Endoscopic examinations including biopsies of the stomach and colon demonstrated the typical subepithelial deposits characteristic of collagenous gastritis and collagenous colitis. Histochemical and ultrastructural methods confirmed the presence of collagen in the subepithelial deposits. The topographic distribution of these collagen deposits and their relationship to the inflammatory process in the stomach were then defined by endoscopic mapping and multiple site biopsies of the mucosa in the gastric body and antrum. These studies indicate that collagenous gastritis not only is distinctive, but also is a far more extensive and diffuse inflammatory process than has previously been appreciated.